Hubungan Digital Marketing Website Terhadap Visit Intention Pasien Rumah Sakit K.H Abdurrahman Syamsury Lamongan - Fandi Ahmad Sanjaya; Nasrudin Nasrudin; Masruroh Masruroh; Meirina Rosa Wisatya (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the relationship between digital marketing website including content quality, user experience, website aesthetics, information accessibility, and social proof on patient visit intention at K.H. Abdurrahman Syamsuri Hospital, Lamongan. The study used an observational analytical design with a cross-sectional approach. The population was all visitors to the hospital website, an average of 3,500 per month, with a sample size of 425 respondents. The results showed that all five were positively and significantly correlated with visit intention (p < 0.001), with the following correlation strengths: social proof (r = 0.472), user experience (r = 0.461), content quality (r = 0.459), website aesthetics (r = 0.446), and information accessibility (r = 0.440). Social proof was the strongest predictor (Wald = 31.665; OR = 0.137). The ordinal regression model simultaneously explained 52.7% of the variation in visit intention (Nagelkerke R² = 0.527).